Nutrition for health and well-being - Anuyahong, Tanisa (Journal of Health Promotion and Environmental Health Research Health Promotion Centre 8 Udon Thani, 2023)
Food and nutrition play a crucial role in health and well-being. Nutrients are essential for growth and development of the body. The quality of food affects physical health, mental health, and emotions. Receiving adequate and appropriate energy and nutrients contributes to growth, immune function, heart and cardiovascular health, and mental well-being. Further, a balance diet can reduce the risk of non-communicable diseases (NCDs) The energy and nutrient requirements depend on age, gender, activity levels, and individual health status. Therefore, it is important to consume a diverse, balanced, and sufficient diet to promote health and well-being. Additionally, engaging in regular physical activity or appropriate exercise is essential to enhance physical fitness, prevent chronic diseases, and metabolic disorders. Moreover, individuals should maintain a healthy lifestyle to sustain long-term health benefits. This will lead to adopting beneficial health behaviors, influencing overall well-being in terms of physical, mental, and enduring wellness